Factors associated with sarcopenia among hospitalised older persons / Mohd Adha Nawawi - Nawawi, Mohd Adha (2023)
This study aimed to 1) compare anthropometry, body composition, physiological measures, psychological function, functional status, length of stay and nutritional status among hospitalised older persons with and without sarcopenia at admission;. 2) compare the effects of hospitalisation on anthropometry, body compositions, physiological measures, psychological functions, and functional status among older persons with and without sarcopenia, 3) identify the association of anthropometry, physiological measures, psychological function, functional status, and nutritional status of hospitalised older persons with and without sarcopenia during admission;.4) determine differences in functional status and quality of life of sarcopenic and non-sarcopenic among hospitalised older persons upon follow-up (post-discharge). This cross-sectional cohort study recruited older patients referred to the Medical Ward, Kuala Lumpur Hospital. Three-time measurements were conducted, namely, at admission (within 48 hours following admission), discharge (a day before discharge or once a plan of discharge is indicated), and post-discharge (3 months after being discharged from the hospital. The independent variables included anthropometric measures (weight [Wt] (kg), height [Ht] (m), body mass index [BMI] (kg/m2) and calf circumference [CC] (cm), muscle mass [MM] (kg) and skeletal muscle index [SMI]) (kg/m2), physiological measures (grip strength HGS(kg), lower limb strength [LLS] (sec) and gait speed [GS] m/s)), psychological function (Cognitive function and depression level), functional status, nutritional status and quality of life [QOL]). Bioelectrical Impedance Analysis was used to measure Wt (kg), BMI and MM. CC and Ht were measured using a tape measure and stadiometer, respectively. HGS, LLS and GS were measured using the handgrip dynamometer and five times sit-to-stand test, respectively. While psychological function, functional status and QOL were measured using the Minicog test, Geriatric Depression Scale [GDS], Barthel Index [BI], Mini Nutritional Assessment [MNA], and EQ5D, respectively. The sarcopenia status (dependent variable) was evaluated using the Asian Working Group for Sarcopenia algorithm (AWGS) to classify participants into sarcopenia and non-sarcopenic. Data analyses were performed using the independent t-tests, Mann-Whitney U test, Wilcoxon signed rank test and binary logistic regression analyses.